Synthesis of the ZnTPyP/WO3 nanorod-on-nanorod heterojunction direct Z-scheme with spatial charge separation ability for enhanced photocatalytic hydrogen generation. Issue 6 (24th January 2023) - Liu, Shuanghong; Xia, Siyu; Wang, Jiefei; Ren, Xitong; Chen, Sudi; Zhong, Yong; Bai, Feng
Abstract : Homogeneous ZnTPyP/WO3 nanorod-on-nanorod Z-scheme photocatalysts are prepared for an enhanced photocatalytic hydrogen generation. This study offers valuable information for preparing organic–inorganic direct Z-scheme photocatalysts. Abstract : The direct Z-scheme photocatalytic system can effectively improve the separation efficiency of photogenerated carriers through the photosynthesis-based photocarrier transport model. In this study, zinc porphyrin-assembled nanorods (ZnTPyP) and WO3 nanorods' nanorod-on-nanorod heterojunctions (ZnTPyP/WO3 ) were successfully prepared through a simple modified acid–base neutralization micelle-confined assembly method using WO3 nanorods as the nucleation template and ZnTPyP as building blocks. ZnTPyP achieved a controllable assembly onto WO3 nanorods through N–W coordination. ZnTPyP/WO3 nanorod-on-nanorod heterojunctions exhibited a structure-dependent photocatalytic performance for hydrogen production. The ZnTPyP/WO3 nanorod-on-nanorod heterojunctions exhibited a optimal hydrogen production rate (74.53 mmol g −1 h −1 ) using Pt as the co-catalyst, which was 2.64 times that of the ZnTPyP self-assembled nanorods. The improvement in the photocatalytic hydrogen production efficiency could be mainly attributed to the direct Z-scheme electron-transfer mechanism from WO3 to ZnTPyP. This is the first report of an approach using porphyrin-assembled nanostructures to construct organic–inorganic Z-scheme photocatalysts. This study offers valuable information for preparing new efficient photocatalysts based on organic supramolecular orderly aggregate materials.